Understanding the motivation of nurses toward the continued use of an evidence-based practice in a tertiary clinical practice setting: An application of planned behaviour theory - Nadalin Penno, Letitia (University of Ottawa (Canada), 2008)
Introduction. In the last two to three decades, research findings have gradually been permeating the culture of nursing. Increasingly, nurses are expected to integrate evidence-based practices into specific nursing policy/protocols and patient care decisions (Polit and Beck, 2004; Rogers, 2004). In truth, research utilization is dependent on nurses' actual direct or indirect use of evidence in the clinical setting (Estabrooks, 1999). To date, researchers have been able to conclude that the more positive a nurse's attitude the more likely the nurse will use research findings (Ehrenfeld & Eckering, 1991; Camiah, 1997; Estabrooks, 1999; Olade, 20203, 2004). The nursing literature reveals a dearth of studies examining nurses' "actual ongoing use" of research and the related factors/challenges affecting their continued use of research findings in clinical practice. Purpose. Why do some nurses continue to use research while others do not where organizational policy supports the ongoing use of evidence-based practice? The purposes of this study are to validate whether nurses' are continuing to use the RNAO's Falls Risk Prevention Best Practice Guidelines (BPG) policy/protocol in 2 units of a tertiary clinical care setting, to examine practicing nurse's attitudes, beliefs and perceptions related to their intention continue to use the policy/protocol; to examine the importance of each variable (beliefs, subjective norms, perceived behavioural controls) related to their intention to continue to use the policy/protocol; and to examine nurses' perceptions and experiences regarding the facilitators, barriers and organizational structures that impact their continued use of research in their practice setting. Methods. This survey correlation design study used Ajzen's Theory of Planned Behaviour (Godin & Kok, 1996) as a theoretical framework to examine practicing nurse's attitudes, beliefs, perceptions related to their intention to continue to use the Registered Nurse's of Ontario Association (RNAO)'s Falls Risk Prevention Best Practice Guideline (BPG) in their clinical practice. Findings. Sixty four percent of surveyed nurses (n=22/44) report using the Falls protocol (a direct type of research) always (18%) and/or often (46%) in their clinical practice. They also reported using the Falls Protocol on their previous shift an average of 2.6 patients per nurse. The main sources of falls research education where nurses first learnt about the RNAO's BPG were during their nursing practice (46%), a form of continuing education (27%), or in a conference/seminar setting (18%). Composite mean scores related to surveyed nurses attitudes, social norm and control beliefs ranged from 1.71 to 2.43 indicating strong positive attitudes, a strong sense of social pressure and greater level of control over their ongoing use of the Falls Protocol in their daily practice. Nurses' attitudes, social and control beliefs explained 46% of the variance in intention related to its ongoing use every 3 months and 73% of ongoing use after a patient fall incidence. Surveyed nurses identified 9 facilitators and 4 potential barriers related to the ongoing use of the Falls Protocol in their clinical practice. Conclusions. Findings reveal nurses in a tertiary care facility demonstrate 'strong generalized intentions' towards the ongoing use of the direct form of research, the Falls Risk Prevention BPG on admission, on a quarterly basis and after a patient fall incident. The 'ongoing utilization of research' in practice is definitely of interest and viewed positively by nurses in this setting despite their educational profile, limited research education and minimal exposure to in-house continuing education. This result indicates exposure to research is necessary in developing favourable attitudes towards RU. Furthermore, nurses' intention to 'continue to use' the Falls Protocol in this tertiary care facility is significantly influenced by the social expectations of referent persons and by their perceived behavioural control (PBC) beliefs. Surveyed nurses also report that three factors facilitate their 'ongoing use' of the Falls Protocol in their setting; these are congruent with those found in the literature relating to the initial adoption of research. These facilitators include: (1) providing research in a usable form; (2) attending conferences or seminars to remain current with new research related to their clinical setting; and (3) engagement in research activities such as the development, updating and implementation of the Falls BPG for use on their units.
Keywords: Health Sciences, Nursing.